Perancangan Sistem Informasi Penjadwalan Produksi Berbasis Engineering to Order di Bengkel Custom Wolfson Motorworks - Yusuf Mauluddin; Ridwan Setiawan; Wibawa Dewantara (Institut Teknologi Garut, 2022)
In the production process of custom motorbikes based on Engineering to Order, it is possible to estimate the time for the production process, but it is not certain when the motorbike will be finished on time, so delays often occur where the estimated time given to consumers does not match the work process time in the field. The purpose of this research is to design a production scheduling information system in the form of a prototype so that builders are able to provide information about the development of the production process in the